Role of Applied Microbiology for Sustainable Agricultural Development in Jharkhand (Indian Journal of Advanced Botany (IJAB), 2025)
Small and marginal farmers in Jharkhand face a range of challenges, including acidic and poorly fertilised soil, irregular rainfall, and recurring attacks by pests and diseases, which significantly restrict agricultural productivity [1]. This review highlights the potential for applied microbiology to be an economically viable and environmentally sustainable approach, utilising soil fertility enhancement, enhancing plant resistance, and reducing the need for synthetic chemicals [2]. Different plant growth-promoting microorganisms (PGPMs), including biofertilizers, phosphate-solubilising bacteria (PSB), arbuscular mycorrhizal fungi (AMF), cyanobacteria, and biocontrol agents such as Trichoderma and Bacillus, were assessed through a rigorous review of indexed research articles on Scopus, Web of Science, and Google Scholar [3]. The results indicate that these microbial products can enhance nutrient-use efficiency by 10 to 25% and stabilise crop yields by 5 to 20% and penetrate the region's soil and climate limitations [4]. The article also includes field-friendly applications of microbial technologies, social innovations like women-inoculant production, and environmental benefits such as improved soil carbon sequestration and reduced chemical use. A plan for scaling up the technologies has been prepared, focusing on quality control, farmer training, and efficient extension services. Overall, this study exemplifies the central role of applied microbiology in advancing sustainable development, food security, ecological balance, and resilient livelihoods for smallholder farmers in Jharkhand.